Periconceptional folic acid supplementation and child asthma: a Right From the Start follow-up study. (12th December 2022) - Adgent, Margaret A.; Vereen, Shanda; McCullough, Alexis; Jones, Sarah H.; Torstenson, Eric; Velez Edwards, Digna R.; Hartmann, Katherine E.; Carroll, Kecia N.
Abstract: Objective: High maternal folic acid exposure has been studied as a risk factor for child asthma with inconclusive results. Folic acid supplementation that begins before pregnancy may propagate high exposures during pregnancy, particularly in regions with fortified food supplies. We investigated whether folic acid supplementation initiated periconceptionally is associated with childhood asthma in a US cohort. Materials and methods: We re-contacted mother–child dyads previously enrolled in a prospective pregnancy cohort and included children age 4 to 8 years at follow-up ( n  = 540). Using first trimester interviews, we assessed whether initial folic acid-containing supplement (FACS) use occurred near/before estimated conception ("periconceptional") or after (during the "first trimester"). Follow-up questionnaires were used to determine if a child ever had an asthma diagnosis ("ever asthma") or asthma diagnosis with prevalent symptoms or medication use ("current asthma"). We examined associations between FACS initiation and asthma outcomes using logistic regression, excluding preterm births and adjusting for child age, sex, maternal race, maternal education, and parental asthma. Results: Approximately half of women initiated FACS use periconceptionally (49%). Nine percent of children had "ever asthma" and 6% had "current asthma." Periconceptional initiation was associated with elevated odds of ever asthma [adjusted odds ratio (95% Confidence Interval): 1.65 (0.87, 3.14)] and current asthma [1.87 (0.88, 4.01)], relative to first trimester initiation. Conclusion: We observed positive, but imprecisely estimated associations between periconceptional FACS initiation and child asthma. Folic acid prevents birth defects and is recommended. However, larger studies of folic acid dosing and timing, with consideration for childhood asthma, are needed.